1990
DOI: 10.1172/jci114746
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced prostaglandin synthesis after ultraviolet injury is mediated by endogenous histamine stimulation. A mechanism for irradiation erythema.

Abstract: Acute ultraviolet light B (UVB) injury is associated with dermal mast cell histamine release. The possibility that histamine-stimulated prostaglandin (PG) synthesis could be a mechanism for irradiation erythema was therefore examined using human skin explants. Explants responded to UV irradiation (120 mJ/cm2) with a fivefold increase in synthesis of prostaglandins E2, F2. and 6-keto PGFIt. Incubating explants with the H1 antihistamines brompheniramine (50 MM) or pyrilamine (30 1AM) inhibited PG release from ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(64 citation statements)
references
References 27 publications
2
61
0
1
Order By: Relevance
“…Other mechanisms by which EP 1 and EP 3 receptor signaling could activate PKCζ include through stimulation of 3-phosphoinositide-dependent protein kinase (PDK1), or through TC10, that activates PKCζ through the scaffold proteins Par3 and Par6 [57,58]. Finally, because UVR up-regulates the production and release of lysophosphatidylcholine and prostaglandins by keratinocytes [59][60][61], activation of PKCζ in response to these paracrine factors may be additive and appears to be an important signaling intermediate in the dendritic response of human to melanocytes to UVR. (25 nM) or misoprostol (500 nM).…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms by which EP 1 and EP 3 receptor signaling could activate PKCζ include through stimulation of 3-phosphoinositide-dependent protein kinase (PDK1), or through TC10, that activates PKCζ through the scaffold proteins Par3 and Par6 [57,58]. Finally, because UVR up-regulates the production and release of lysophosphatidylcholine and prostaglandins by keratinocytes [59][60][61], activation of PKCζ in response to these paracrine factors may be additive and appears to be an important signaling intermediate in the dendritic response of human to melanocytes to UVR. (25 nM) or misoprostol (500 nM).…”
Section: Discussionmentioning
confidence: 99%
“…A similar mechanism exists in the mouse urinary bladder, where urinary epithelial cell TRPV1 is required for hypoosmolarity-evoked release of ATP (37), which in turn appears to be detected by P2X3 (ATP-gated ion channel subtype three)-containing nerve terminals in the bladder wall (42). Alternative candidate heat-evoked signaling molecules include nitric oxide, which also undergoes TRPV1-dependent release from urinary epithelial cells (43), as well as prostaglandins and platelet-activating factor, which have been shown to be released from keratinocytes in response to UV radiation (44), extreme heating, oxidative stress (25), or, in human keratinocytes, capsaicin-evoked activation of TRPV1 (21). Biochemical analysis of supernatants from warmth-treated keratinocytes would allow the "soluble messenger" hypothesis to be tested experimentally, as would the analysis of thermosensation and thermoregulation in mice lacking TRPV4 selectively in keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Beside these physiological and bene®cial e ects, the solar U.V. light also causes pathological and noxious e ects including skin erythema (Pentland et al, 1990), premature skin aging (Fisher et al, 1996) and skin cancer (Ananthaswamy and Pierceall, 1990). Recently, many studies have been undertaken to elucidate the cellular signaling pathways triggered by U.V.…”
mentioning
confidence: 99%
“…The role of ERKs and SAP kinases activation in U.V.-A and U.V.-B responses is not clearly understood. However, U.V.-induced skin injury is followed by an enhanced prostaglandin synthesis that contributes to the in¯ammatory response (Pentland et al, 1990). The activity of phospholipase A 2 (PLA 2 ) that controls prostaglandin synthesis (Nakazato et al, 1991) has been reported to be stimulated after phosphorylation by MAP kinases (Qiu and Leslie, 1994).…”
mentioning
confidence: 99%